A new species of the Brazilian genus Chresta (Asteraceae, Vernonieae) from Bahia - Roque, Nádia (2008)
A new species of the genus Chresta Vell. ex DC. (Vernonieae,Asteraceae) from the Brazilian state of Bahia is described and illustrated. The new species resembles Chresta pinnatifida (Philipson) H.Rob. but differs in having solitary glomerules, leaf bases clasping the stem and 35-40 capitula per glomerule. It can be distinguished from Chresta harleyii and Chresta martii, the other two species of the genus with pinnately lobed leaves, by the type of pubescence, leaf blade bases and florets number. In addition, a key to distinguish all the species of the genus is presented. © 2008 The Linnean Society of London, Botanical Journal of the Linnean Society, 2008, 157, 587-590.